Entrepreneurship and economic growth - Carree, Martin Anthony; Thurik, A. R. (A. Roy). (Northampton, Mass. : Edward Elgar, 2006)
This book provides a general overview along with historical and country specific studies articles on entrepreneurship and innovation; details of endogenous growth models in which enterpreneurship plays a vital role; contributions on competition and productivity; and empirical evidence.
Includes bibliographical references and index.
aug 09/05/13
Loans
Keywords: Entrepreneurship; Economic development